Formation Of Stable Gold Nanoparticles Via Laser Ablation Conjugated In-Situ By BSA In Harsh Saline Condition For Cells Antiproliferative Activity - Abdulateef, Sinan Adnan (2018)
Colloidal AuNPs is known to aggregate and precipitate in the saline solution below the NaCl concentration of many bodily fluids and blood plasma. This research focused on the preparation of high stability and bioactivity colloidal gold nanoparticles (AuNPs) in simulated body fluid (SBF), which can closely mimic the blood plasma that is free from contamination through a low-cost technique that can be done at room temperature within a short period of time. To achieve this aim, the following three specific objectives were designed; Firstly, to produce a high stability colloidal suspension of AuNPs in media close to blood plasma by using pulse laser ablation synthesis techniques.